Greener synthesis of electrospun collagen/hydroxyapatite composite fibers with an excellent microstructure for bone tissue engineering - Zhou YY (Dove Medical Press, 2015)
Yuanyuan Zhou,1,2 Hongchang Yao,1 Jianshe Wang,1 Dalu Wang,1 Qian Liu,1 Zhongjun Li11College of Chemistry and Molecular Engineering, Zhengzhou University, Zhengzhou, People’s Republic of China; 2Institute of Enviromental and Municipal Engineering, North China University of Water Resources and Electric Power, Zhengzhou, People’s Republic of ChinaAbstract: In bone tissue engineering, collagen/hydroxyapatite (HAP) fibrous composite obtained via electrospinning method has been demonstrated to support the cells’ adhesion and bone regeneration. However, electrospinning of natural collagen often requires the use of cytotoxic organic solvents, and the HAP crystals were usually aggregated and randomly distributed within a fibrous matrix of collagen, limiting their clinical potential. Here, an effective and greener method for the preparation of collagen/HAP composite fibers was developed for the first time, and this green product not only had 40 times higher mechanical properties than that previously reported, but also had an excellent microstructure similar to that of natural bone. By dissolving type I collagen in environmentally friendly phosphate buffered saline/ethanol solution instead of the frequently-used cytotoxic organic solvents, followed with the key step of desalination, co-electrospinning the collagen solution with the HAP sol, generates a collagen/HAP composite with a uniform and continuous fibrous morphology. Interestingly, the nano-HAP needles were found to preferentially orient along the longitudinal direction of the collagen fibers, which mimicked the nanostructure of natural bones. Based on the characterization of the related products, the formation mechanism for this novel phenomenon was proposed. After cross-linking with 1-ethyl-3-(3-dimethyl-aminopropyl)-1-carbodiimide hydrochloride/N-hydroxysuccinimide, the obtained composite exhibited a significant enhancement in mechanical properties. In addition, the biocompatibility of the obtained composite fibers was evaluated by in vitro culture of the human myeloma cells (U2-OS). Taken together, the process outlined herein provides an effective, non-toxic approach for the fabrication of collagen/HAP composite nanofibers that could be good candidates for bone tissue engineering.Keywords: collagen, hydroxyapatite, electrospinning, nanofibers, biomaterials